Lessons learned and functional outcomes following multifaceted team training in a cognitive strategy-based approach to stroke rehabilitation. Issue 1 (14th March 2022) - Rios, Jorge; Linkewich, Elizabeth; Allen, Kay-Ann; Egan, Mary; Dawson, Deirdre R.; Godleski, Matthew; Hunt, Anne; Jutzi, Katelyn; Quant, Sylvia; McEwen, Sara E.
ABSTRACT: Aim: To estimate the impact of a multifaceted knowledge translation intervention on patient rehabilitation outcomes in an inpatient stroke setting. Methods: Interprofessional stroke rehabilitation teams were trained in Cognitive Orientation to daily Occupational Performance as part of the larger knowledge translation study. This study describes a two group (historical control vs. post knowledge translation intervention) nonrandomized study. Patient participants with stroke and cognitive impairment were recruited from five rehabilitation hospitals and completed an assessment battery upon admission to and discharge from rehabilitation and at three follow-up times. Data were analyzed using a two-way ANOVA. Results: Seventeen historical controls and eight postintervention participants were recruited. The effect for time was significant ( P  ≤ 0.05) for the majority of outcomes, but there were no significant group × time effects. Small effect sizes for the group × time interaction were noted on several indicators. Conclusion: Few studies report on patient outcomes following a knowledge translation intervention. Small effect sizes were detected on several patient outcomes, despite study limitations. Lessons learned for future patient-level studies within knowledge translation interventions include the importance of monitoring therapist adherence to implementation protocols and ensuring research designs consider the impact on patient recruitment and retention.